2017
DOI: 10.1080/01612840.2016.1269856
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Associated with Inpatient Psychiatric Re-admissions and the Utility of the READMIT Clinical Risk Index

Abstract: In response to the problem of frequent 30-day readmissions to inpatient psychiatric facilities, Vigod and colleagues (2015) developed the READMIT clinical risk index to identify risk factors for psychiatric inpatient readmissions. The purpose of this descriptive retrospective study was to examine the effectiveness of the READMIT clinical risk index to identify patients that are at high risk for a 30-day inpatient psychiatric readmission at a state psychiatric hospital in the southeastern US. Data were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…35,47 However, other papers have found that depot medications had no association with the risk of readmission. 14,48 Depot medications are sometimes prescribed for patients with a high risk of poor drug adherence, which some have suggested to be the cause for relapse. However, some pieces of research have failed to find an association, suggesting that medication non-adherence is more likely to be associated with delayed readmissions to psychiatric units, rather than rapid readmissions such as the time frame of 28 days used in this study.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…35,47 However, other papers have found that depot medications had no association with the risk of readmission. 14,48 Depot medications are sometimes prescribed for patients with a high risk of poor drug adherence, which some have suggested to be the cause for relapse. However, some pieces of research have failed to find an association, suggesting that medication non-adherence is more likely to be associated with delayed readmissions to psychiatric units, rather than rapid readmissions such as the time frame of 28 days used in this study.…”
Section: Main Findingsmentioning
confidence: 99%
“…13 The model was then applied to a different group of patients in south-eastern USA with good predictive ability. 14 Risk models are already being deployed in some countries. Scotland has deployed a risk model to calculate the risk of readmissions for all diagnoses, including psychiatric hospital readmission.…”
Section: Aimsmentioning
confidence: 99%
“…They concluded that recording medication compliance in the EMR is important for identifying atrisk patients. Electronic tracking was echoed by Roque, Findlay, Okoli, and El-Mallakh (2017), who also reported that patients with chronic mental health issues need clinical screening for risk of readmission to reduce 30-day readmission rates. Tiihonen et al (2017) studied the effectiveness of various antipsychotic formulations (i.e., LAIs vs. oral medications).…”
Section: Available Knowledgementioning
confidence: 99%
“…Known as a dual diagnosis, an estimated one third to one half of adults diagnosed with a mental illness also have a substance use disorder (Antai-Otong, Theis, & Patrick, 2016;Drake, Mueser, & Brunette, 2007; European Monitoring Centre for Drugs and Drug Addiction [EMCDDA], 2015; Petrakis, Robinson, Myers, Kroes, & O'Connor, 2018). Also referred to as having a concurrent disorder or a co-occurring disorder (EMCDDA, 2015), individuals in this subgroup face many challenges including being more likely to have added health problems (Drake et al, 2006;Rosenberg, Drake, Brunette, Wolford, & Marsh, 2005) as well as being at increased risk for adverse outcomes, including treatment nonadherence and suicide (Beeber & Stein, 2015;Cosci & Fava, 2011;Czobor et al, 2015;Drake, O'Neal, & Wallach, 2008;Greenberg & Rosenheck, 2014;Jacobs et al, 2010;Krausz et al, 2013;Montes, Maurino, de Dios, & Medina, 2013;Roque, Findlay, Okoli, & El-Mallakh, 2017;Sendt, Tracy, & Bhattacharyya, 2015). The frequency of emergency room visits as well as hospital readmission rates and length of stay are significantly higher for patients with a dual diagnosis than for those with either a mental illness or a substance use disorder alone (Antai-Otong et al, 2016;Cosci & Fava, 2011;Drake et al, 2008;Jacobs et al, 2010).…”
Section: Introductionmentioning
confidence: 99%